Pengaruh Belanja Ekonomi di Era Desentralisasi Fiskal terhadap Kemiskinan di Indonesia - Zainuddin, Zainuddin; Hamdani, Hamdani; Ilyas, Ilyas; Maryam, Maryam (Lembaga KITA, 2021)
The purpose of this study was to determine the effect of provincial government sectoral spending on poverty in the era of fiscal decentralization in Indonesia. Meanwhile, the sectoral expenditure variables that are considered closely related to poverty are economic spending, housing and public facilities spending, health spending, education spending, and social protection spending according to provinces in Indonesia. The data in this study is panel data, namely cross-section of 33 provinces, and time series of 4 years, namely the period 2012 - 2015. After the Chow test and Hausman test, as well as the lagrange multiplier test, the analysis model in this study was determined to be the random effect model, which is a common analysis model in panel data analysis. This study concludes that partially negative economic spending on poverty, meaning that sector spending can reduce poverty in the era of fiscal decentralization in Indonesia. In this analysis, it was found that the ability of the independent variable in explaining the dependent variable was 0.190165 units or 19.02%, and the remaining 80.98% was explained by other variables not included in this study.